Reflections to the Problem of the Nature of Creativity. (Journal of Educational Sciences, 2017)
This article describes the problems of the nature of creativity, analysis of factors that contribute to creativity, such as genetics, education, the age and time, and their influence on the formation and development of thecreative personality. The author notes that the problem of creativity is the subject of study of various sciences, as creativity, as a phenomenon is observed in different spheres of human activity, such as art, science,  ducation. The article presents the theory in the field of psychology of creativity, philosophy of education. None of the factors of creativity is not dominant in the creative process. Successful creative potential depends on the totality of the factors. The article was prepared within the scientific research project of the Ministry of Education and Science of the Republic of Kazakhstan No 1763/ GF4 «The Development of creativity and creative abilities of students as the factor of increase of intellectual potential of Kazakhstan». The factors that contribute to creativity: genetics, culture and development of society, education.
Keywords: art; nature art; creativity